A rare coronary anomaly consisting of a single right coronary ostium in an adult undergoing surgical coronary revascularization: a case report and review of the literature. (December 2016) - Prifti, Edvin; Ademaj, Fadil; Krakulli, Klodian; Rruci, Edlira; Zeka, Merita; Demiraj, Aurel
Abstract Background Coronary arteries originating from the right coronary ostium in the ascending aorta represent a very rare anatomic presentation. Also, the presence of a single coronary ostium is an extremely rare finding. Case presentation We present the case of a 74-year-old Albanian man from Kosovo. He had unstable angina due to critical triple vessel disease and a single coronary artery originating from a single ostium in the right sinus of Valsalva with an anomalous course of his left anterior descending artery anteriorly to the right ventricular outflow tract as a "T-vessel" from which originated the proximal and distal left anterior descending artery, the circumflex artery originating from the mid portion of the right coronary artery which had a normal course. He underwent successful coronary revascularization consisting of three vein grafts to the right coronary artery, first diagonal and obtuse marginal artery, and left internal mammary artery anastomosed to left anterior descending artery. Conclusions We describe a proposed IID1 pattern. After a careful revision of the literature, only six cases have been reported with a similar anomalous coronary origin. Only two out of six patients underwent surgical coronary revascularization. In our case the aberrant vessel arising from his right coronary artery coursed anteriorly to the right ventricle and continued as a left anterior descending artery at its mid portion which then continued distally as the distal left anterior descending artery and proximally as a proximal left anterior descending artery, having the shape of a "T vessel". The "T-vessel" configuration has never been reported in the literature. The reported case with its specific presentation adds further information on this rare form of anomalous origin of the coronary arteries, representing a first report of a configuration that we name the "T-vessel" of the left anterior descending artery. Diagnosis of the coronary anatomy is very important for the invasive cardiologist and cardiac surgeon in cases with a single coronary ostium, such as our case, so that they can proceed with the invasive or surgical treatment when critical coronary artery disease is present.